Improvement of the method for calculation of bonus payments of employees at mining stations of coal mines - Пістунов, Ігор Миколайович; Пономаренко, Олексій Павлович (Technology audit and production reserves, 2016)
The formula for determining bonus payment to the basic rate of the miner depending on the percentage of the plan and ash content of coal was defined in the article. The workers and middle managers of Western Donbas mines were interviewed for this purpose that determined separately level of bonus payment, depending on the percentage of the plan and the level of its adjustments based on the achievement of the required level of coal ash. Moreover, shortfalls of plan to 80 % isn’t determined zero bonus payment. At the same time, the deviation of ash content more than 47 % is determined the bonus payment equal to zero. Research was conducted in connection with reduction of the competitive cost of Ukrainian coal compared with imported coal and the need to reduce its costs and increase quality. As a result, it was found that the experts have identified the required level of interest allowances with sufficient consistency of opinions (Kendall coefficient 0,743 and 0,84). Piecewise linear approximation was used to create a single formula for calculation of bonus payments that ensured its absolute accuracy. The result allows stimulating the miners’ work towards reducing the cost of coal and reducing its ash content, and because the method is based on the opinions of coal experts, it must really influence the process of coal production in Ukraine. Implementation of methodology for SE «Selydiv coal» for mining station № 2 has increased the coal production by 1,6 times, reduced the ash content of coal in 3,4 times and increase the wages of workers by 12,2 %.